The influence of work motivation and leadership style on employee performance - Inna Nisawati Mardiani; Riki Chandra (Journal of Economics and Business Letters, 2022)
Performance is the result of work achieved by someone who is adjusted to their respective roles or tasks in a company at a certain time period, which is associated with a certain value or standard measure of the company where the person works. This study aims to determine the effect of work motivation and leadership style on employee performance. The type of research used is quantitative, with a population of all 45 employees of PT Pusaka Kali Agung and sampling using a saturated sample technique. This research uses validity test, reliability test, classical assumption test, multiple linear regression analysis and determination (adjusted R2) . The results in this study explain that work motivation and leadership style affect employee performance.